Unveiling the mechanisms of carbon conversion and loss in biochars derived from characteristic lignocellulosic biomass. Issue 5 (October 2022) - Wan, Jiang; Liu, Lin; Wang, Gehui; Sang, Li; Liang, Weiyu; Zhang, Wei; Peng, Cheng; Fu, Rongbing
Abstract: The relationship between biomass components and carbon retention or loss in biochars is unclear. In this study, four characteristic feedstocks were pyrolyzed into biochar, and the conversion and stability of carbon in biochar were studied in detail. Thirteen kinds of ion fragments were detected by thermogravimetry - mass spectrometry (TG-MS), among which H2 O, CO2 and CO were the main gas products. In addition, the presence of lignin slowed that the pyrolysis of biomass and produced more CO, which eventually led to more aromatic biochar. The carbon retention of lignin, cellulose and xylan during pyrolysis was 78.7 %, 41.7 % and 40.2 %, respectively. Carbon retention calculations showed that lignin was a major contributor to the formation of biochar (40.1–53.2 %). In the K2 Cr2 O7 oxidation experiment, the carbon stability of sunflower and cotton stalk char was relatively poor, which was consistent with the results of thermal stability. Spectral characterization analysis showed that biomass with low lignin content generated more unstable carbon during pyrolysis, which was more likely to be lost or converted in an oxidized environment. These findings are meaningful for guiding in biochars preparation and avoiding their environmental risks. Graphical Abstract: ga1 Highlights: Lignin-rich biomass tended to release more CO than CO2 during pyrolysis. Lignin was a major contributor to the carbon retention in biochars (40.1–53.2 %). Biochars derived from biomass richer in lignin had a stronger stability. The heterogeneity of biochars resulted in loss of unstable aliphatic carbon.